THE IMPLEMENTATION OF TEACHING-LEARNING JAVANESE LANGUAGE (FAIRY TALE STORY) BASED ON HONEST CHARACTER EDUCATION IN CURRICULUM 2013 - Prima Veronika; Budhi Setiawan; Nugraheni Eko Wardani (Universitas Sebelas Maret, 2017)
The study aimed to discuss the implementation of teaching-learning Javanese language (fairy tale story) based on honest character education in the curriculum 2013. The type of this research is qualitative research with single case study approach. The results showed that teaching-learning Javanese language (fairy tale story) can instill honest character education through role playing learning model with scientific approach. The steps of learning model role playing with scientific approach include role playing activities based on observing activities, asking questions, gathering information, associate, try, and communicate.